The Education of Women During the Qājār Period: the Contribution Provided by the Works of Fénelon and Madame de Lambert (Altre Modernità, 2019)
This work aims at presenting the new educational materials proposed byPersian translators and foreigner authors such as Fénelon and Madame de Lambertwhose works focused on woman’s genuine role within the Islamic community and onnew cultural ideals where men should have a different attitude towards women in orderto grow the new generation according to healthy and renewed principles. Through thecomparative and intertextual method, this research traces the links between texts anddifferent influences. It will be shown how Persian authors have been inspired by Frenchwriters belonging to previous literary traditions to conciliate tradition and progress.